PENGARUH KETAHANAN KEUANGAN TERHADAP PENERAPAN ETIKA AKUNTANSI DI KALANGAN MAHASISWA AKUNTANSI UNIVERSITAS 17 AGUSTUS 1945 SURABAYA - Febri Risnandia; Hwihanus, Hwihanus (Cahaya Ilmu Bangsa, 2024)
This research aims to analyze the influence of financial resilience on the application of accounting ethics among accounting students. Financial resilience, which reflects an individual's ability to manage their financial resources, is considered an important factor that can influence the way students understand and apply ethical principles in accounting. This study uses a survey method involving accounting students from several universities as respondents. Data was collected through a questionnaire measured using a Likert scale, then analyzed using linear regression to test the relationship between financial resilience and the application of accounting ethics. The research results show that financial resilience has a significant positive influence on the application of accounting ethics. Students with a better level of financial resilience tend to have a higher understanding and application of ethics in accounting practice. This conclusion provides important implications for educational institutions in designing accounting ethics education programs that consider students' financial resilience factors.